Futureproof : security aesthetics and the management of life - Ghertner, D. Asher; McFann, Hudson, 1987-; Goldstein, Daniel M., 1965- (Global insecurities., 2020)
"From terrorism and public health to museums, schools, and homes, FUTUREPROOF asks us to expand our purview of security, turning our attention to how security is lived, felt, and perceived through the violences of everyday life. Editors Asher Ghertner, Daniel Goldstein, and Hudson Fann propose the modality of "security aesthetics" as a way to understand how sensory and affective experiences help regulate bodies, spaces, and states in the service of "futureproofing" society against anticipated risks and perils. Taken broadly as the domain of sense perception, aesthetics provides a framework for considering the body's interactions with the material world and the processes by which these interactions translate into subjective judgments of taste. The contributions to this volume show us how security aesthetics work to fashion differently imagined futures, illuminating the interplay of sense perception and articulated reason in the operations of security apparatuses"--